Fragmentation of lignin from organosolv black liquor by white rot fungi - Negrão, Djanira R.; Sain, Mohini; Leão, Alcides L. [UNESP]; Sameni, Javad; Jeng, Robert; De Jesus, João P.F. [UNESP]; Monteiro, Regina T.R. (BioResources, 2015)
The mycelial growth ability of 13 white rot fungi were separately evaluated in kraft, organosolv, and soda black liquor agar-plates. The fungus able to best grow and decolorize black liquor agar-plates was grown in organosolv black liquor to investigate whether it reduced organosolv lignin molar mass. The fungus Bjerkandera adusta showed fair mycelial growth and decolorization ability in 10% black liquor-agar plates. To obtain low-molecular weight (MW) lignin, B. adusta was cultivated in 150-mL Erlenmeyer flasks containing 10% black liquor and maintained in a shaking culture for 15 days. Lignin was recovered from each Erlenmeyer flask by acid precipitation and was analysed by size exclusion chromatography (SEC) and Fourier transform infrared (FTIR) spectroscopy. The lowest MW of lignin from black liquor was observed on the 11th and 12th days, at 1461 and 1790 kDa, respectively, with the polydispersity close to 1.0, indicating that the molecules were similar in size. Fourier transform infrared spectra bands showed modification of the lignin structure during 9 days, with new bands appearing after five days of lignin biodegradation.
Keywords: Black liquor; Decolorization; Lignin; Molecular weight; White-rot fungi